2013
DOI: 10.1007/s00213-013-3133-6
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin depletion counteracts sex differences in anxiety-related behaviour in rat

Abstract: Serotonin depletion abolishing the sex differences observed at baseline supports the theory that serotonin aids to uphold certain sex differences in behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…This method almost completely eliminated Tph2 and 5-HT immunoreactivity in the dorsal raphe nucleus. Importantly, AADC, norepinephrine, and dopamine levels were unaffected, at least at 2 weeks after injection.The disruption of the 5-HT machinery selectively in serotonergic neurons not only confirmed previous findings regarding its role in sleep-wake cycles and locomotor activity (Alenina et al, 2009), but also revealed novel physiological and behavioral consequences. Although classical measures of anxiety-like behavior (i.e., time spent in bright/unprotected vs dark/ protected areas) were not affected by 5-HT depletion, a marked increase in locomotor activity in the open field was found.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…This method almost completely eliminated Tph2 and 5-HT immunoreactivity in the dorsal raphe nucleus. Importantly, AADC, norepinephrine, and dopamine levels were unaffected, at least at 2 weeks after injection.The disruption of the 5-HT machinery selectively in serotonergic neurons not only confirmed previous findings regarding its role in sleep-wake cycles and locomotor activity (Alenina et al, 2009), but also revealed novel physiological and behavioral consequences. Although classical measures of anxiety-like behavior (i.e., time spent in bright/unprotected vs dark/ protected areas) were not affected by 5-HT depletion, a marked increase in locomotor activity in the open field was found.…”
supporting
confidence: 84%
“…Indeed, patients carrying a polymorphism of the Tph2 gene show higher susceptibility to develop ADHD (Sheehan et al, 2005). Accordingly, mice lacking the 5-HT transporter show higher 5-HT extracellular levels (Kim et al, 2005) and lower locomotor activity than controls (Kalueff et al, 2007). The hyperactive phenotype described by Whitney et al…”
Section: Fl/ϫmentioning
confidence: 99%
See 3 more Smart Citations